JPJ Speed Tracker / Hazami Zulkifli, Muhammad Aiman Shaari and Mohamad Nor Efiezal Mukminin Mohd Fadzil - Zulkifli, Hazami; Shaari, Muhammad Aiman; Mohd Fadzil, Mohamad Nor Efiezal Mukminin (2018)
Our team is developing a device called "JPJ Speed Tracker". The main purpose of this project is to monitor the speed, location of public transport specifically express buses and it "transmit instant signal to authorities if an accident happen to the public transports. It is a small and portable device consisting of accelerometer that monitor and detect the speed of vehicle, a Global Positioning System (GPS) for determining the position of where the bus located across the globe and the most important thing is a signal transmitter, where all the information will be transmit, send to Jabatan Pengangkutan Jalanraya (JPJ) and other authorities. Our project also includes the development of a receiver software, where all the information of gathered by the device will be received and can be observed using the software. Hence, authorities can monitor the movement of our public the bus and in the same time make sure if they exceed any speed limit or anything happen to the bus, they can intantly oin point the location and give quick action. Our survey on 20 authorities including polices, JPJ personnel and regular public transport user, they think that this product suitable to be installed in our express bus and it should make the our bus much safer because as our Ministry of Transport said on its interview by The Star "We are quite perturbed by the rate of accidents happening on these roads,".